Lifetime Modulation of the Pain System via Neuroimmune and Neuroendocrine Interactions - Zouikr, Ihssane; Karshikoff, Bianka (Frontiers in Immunology, 2017)
Chronic pain is a debilitating condition that still is challenging both clinicians and researchers. Despite intense research, it is still not clear why some individuals develop chronic pain while others do not, or how to heal this disease. In this review, we argue for a multisystem approach to understand chronic pain. Pain is not to be viewed simply as a result of aberrant neuronal activity, but also as a result of adverse early life experiences that impact an individual’s endocrine, immune and nervous systems, changes which in turn program the pain system. First, we will give an overview of the ontogeny of the central nervous system (CNS), endocrine, and immune systems and their windows of vulnerability. Thereafter, we summarize human and animal findings from our labs and others that point to an important role of the endocrine and immune system in modulating pain sensitivity. Taking “early life history” into account, together with the past and current immunological and endocrine status of chronic pain patients, is a necessary step to understand chronic pain pathophysiology and assist clinicians in tailoring the best therapeutic approach.